The Effectiveness of Depression Intervention and Risk Factor in Geriatrics: a Systematic Review - Sunarti, Sri; Rakha, Muhammad; Harumbay, Nysrina; Harahap, M.; Hidayat, Rizal (Universitas Brawijaya, 2023)
Background: Increasing age is a new challenge in today's health services. With increasing age, the physiological function will decrease. Not only infectious diseases and systemic diseases, but the elderly are also prone to social problems and mental health problems, including depression. Depression is the most common mental illness in the elderly. Depression can significantly reduce the quality of life of the elderly. Aim: To obtain a deeper understanding of interventions and risk factors for depression in geriatrics.Methods: Literature searches were taken from Science Direct, Pubmed, and Google Scholar from 2020 - 2022, in which 8 eligible articles were found. The keywords used in the search were